Taktfull ledelse i barnehagen - Ohm, Modgun; Grindheim, Liv Torunn (Forskning i Pædagogers Profession og Uddannelse, 2024)
Early childhood teachers strive to balance the planned and the spontaneous, when valuing both here-and-now and responsibilities to pass on established knowledge. This cause challenges when emphasizing children right to influence their daily practices. We ask: How can early childhood teachers balance tensions between the planned and the spontaneous when carrying out activities? An early childhood teacher’s narrative about changing the tour day based on the initiative from a five-year-old child, forms our empirical material. The material is analyzed based on van Manens four pedagogical ways of teaching: pedagogical sensitivity, sense, sensibility, and acting. The analysis surfaces how balancing closeness and distance is central. However, the emphasis on the spontaneous left possibilities to expand the content on the tour day, in the shadow. Abstract Barnehagelærere står i spenn mellom det planlagte og det spontane, mellom verdsetting av her-og-nå og ansvaret for å videreformidle etablert kunnskap. Det gir utfordringer når barn skal være deltagende i planlegging og vurdering av barnehagens virksomhet, og reiser spørsmålet: Hvordan kan barnehagelærere balansere spenninger mellom det planlagte og det spontane i gjennomføring av aktiviteter? Materiale for analyse er en barnehagelærers narrativer om forandring av turdagen initiert av femåringer. Materialet blir analysert i lys av van Manens fire pedagogiske væremåter; pedagogisk sensitivitet, sans, følsomhet og handling. Analysen viser hvordan balansering av nærvær og distanse ble sentralt. Samtidig viser analysen at vektlegging av taktfull ledelse skygget for utvidelse av innholdet på turdagen.